Halal certification mechanism for Sharia hotels in the development of Muslim-friendly tourism under Job Creation Law - Allya Shifa Akhsanty; Ro'fah Setyowati; Aisyah Ayu Musyafa; Muthia Eka Destyana (Universitas Muhammadiyah Magelang, 2023)
The development of the global halal industry is increasing and has received positive responses from various parties. Indonesia as a country that already has a culture that is attached to the halal lifestyle has the opportunity to develop its leading sector, namely Muslim-Friendly Tourism. Therefore, it requires attention and participation from stakeholders in the tourism sector such as the government and business actors in the tourism industry. In order to encourage the realization of economic improvement through Muslim-friendly tourism, halal certification instruments are needed in several units, one of which is a restaurant in a sharia hotel. The purpose of this study is to analyze the halal certification mechanism, especially in the Islamic hotel restaurant unit based on the Job Creation Law. In order to discuss this topic, this research uses normative juridical methods, utilizing secondary data, consisting of primary legal materials and secondary legal materials. This study found that there are fundamental changes related to the halal certification mechanism for business actors, including Islamic hotels under Job Creation Law. The changes referred to are in the mechanism and flow of issuing halal certification. Before the Job Creation Law, halal certification was processed over a long period of time and the applicant was charged a fee in the process. Meanwhile, under the Job Creation Law, the process of issuing halal certification is accelerated and services are expanded. This can encourage the development of Muslim-friendly tourism in Indonesia.